1994
DOI: 10.1063/1.356504
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Mo contacts to CuInSe2 for improved adhesion in photovoltaic devices

Abstract: An electrical contact material consisting of an initially metastable solid solution of Cu in MO is shown to provide improved adhesion to CuInSez when the Cu content exceeds -30 at. %. During physical-vapor deposition of CuInSea on these Cu-MO solutions at elevated temperatures, phase separation occurs and Cu is released into the CuInSez layer. The Cu release begins at approximately 450 "C! and increases in rate with increasing temperature. The release of Cu into the film along with consequent changes in the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The use of an alloy (Mo,Cu) contact to improve adhesion has also been demonstrated. 298 Despite its widespread acceptance for this function, the Mo/p-CIS contact may not be purely Ohmic. Studies have shown that there exists a small Schottky barrier between them, 299 which has no effect on the device's I-V characteristics when operated in the PV mode under normal conditions.…”
Section: Ohmic Contactsmentioning
confidence: 99%
“…The use of an alloy (Mo,Cu) contact to improve adhesion has also been demonstrated. 298 Despite its widespread acceptance for this function, the Mo/p-CIS contact may not be purely Ohmic. Studies have shown that there exists a small Schottky barrier between them, 299 which has no effect on the device's I-V characteristics when operated in the PV mode under normal conditions.…”
Section: Ohmic Contactsmentioning
confidence: 99%
“…[7][8][9][10][11][12] For example, in 1985, Dirks and Broek found that vapor-deposited Cu 100Ϫx Mo x thin films exhibited a bcc structure when 30рxϽ100 and had an fcc structure when 0Ͻxр20. They also observed that the electrical resistivity of Cu-Mo alloys increased with the alloy concentration when 0рxр50 and decreased when 50Ͻxр100.…”
Section: Introductionmentioning
confidence: 99%
“…% Cu could provide a significantly enhanced adhesion to the CuInSe 2 substrate, resulting in improving the uniformity as well as the performance of the photovoltaic devices. 9 Considering the above background, the immiscible Cu-Mo system is thus selected as a model system for the present study. To the authors' knowledge, there is no realistic n-body potential or ab initio calculation reported for the Cu-Mo system in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…%) targets along with simultaneous evaporation of selenium (Se). This is a modification of the previous process used for these films [8] with the addition of the copper source, allowing for greater flexibility in the process. Film depositions were performed at an Ar pressure of 2 mTorr with constant rates for the metal fluxes and the selenium.…”
Section: Methodsmentioning
confidence: 99%
“…One means to accomplish this goal is by introduction of a hybrid process for the deposition of the Cu(In,Ga)Se 2 layer using both cosputtering of the metals and evaporation of the selenium. To the best of our knowledge, device fabrication using a similar hybrid process has not been actively pursued since 1995, having achieved an efficiency near 10% on a small area device [8]. In this study, we will present results on the hybrid deposition and characterization of Cu(In,Ga)Se 2 thin films and solar cells and will compare these results with those from solar cells in which the Cu(In,Ga)Se 2 is purely coevaporated.…”
Section: Introductionmentioning
confidence: 99%